The Effects of Turats Learning, AI, Digital Literacy, Spiritual Leadership, and Collaboration on Santri Achievement through Engagement - Siti Lathifatus Suniyah; Ariefah Sundari; Ahmad Jarullah El-Khotib; Khotib Khotib (Pascasarjana Universitas KH. Abdul Chalim, 2026)
The development of digital technology has transformed learning systems in Islamic boarding schools. Santri no longer rely solely on traditional kitab-based learning but also utilize digital technology and artificial intelligence in daily academic activities. This study aims to analyze the effects of Turats Learning, AI Assisted Learning, digital literacy, spiritual leadership, and collaborative learning on santri academic achievement through student engagement. The research employed a quantitative approach using a survey method involving 250 santri from several modern Islamic boarding schools in East Java, Indonesia. Data were collected through questionnaires distributed using purposive sampling techniques. Data analysis was conducted using Partial Least Square Structural Equation Modeling (SEM-PLS). The hypotheses examined both direct and indirect relationships among the variables. The findings reveal that Turats Learning and digital literacy have strong effects on student engagement and santri academic achievement. AI-assisted learning and collaborative learning also significantly improve student participation in the learning process. This study contributes to the development of an adaptive Islamic boarding school education model that integrates digital transformation while maintaining spiritual values and traditional Islamic learning culture. The findings highlight the importance of balancing modern technology with pesantren academic traditions to improve the quality of santri education.